Simple RAM Control for Water Strider Robot - Chun, Kyunghan; Kim, Bonghwan (International Journal of Engineering and Technology, 2018)
In this paper, we propose a RAM (Rotate and Move) controller by considering the WSR (Water Strider Robot) with two wheels. The proposed controller commands to move straight after rotating to track the desired trajectory by applying the two wheel WSR characteristics. In this paper, a proportional controller is applied to make the error zero and there is a room to apply many other nonlinear controllers. For a given target point, the rotation angle is computed at first and the shorter rotating angle is chosen between CW (clockwise) and CCW (counterclockwise). After accomplishing rotation, the WSR moves straight toward the target point. The proposed controller is noble and simple and easily track the target point and the simulation results proves the good performance and this controller will be applied to the developing prototype WSR.Â Â